An Analysis of Learning Difficulties on Mathematic at Elementary School - Muh. Yazid; Atiaturrahmaniah Atiaturrahmaniah; Mita Armila (International Journal on Advanced Science, Education, and Religion, 2020)
This article aims at finding out the factors of Mathematic learning the difficulty of class v at Elementary School in Melati cluster kerumut village academic year 2020/2021. This study was a qualitative descriptive study. The population of this study was class V students in melati cluster kerumut village such as SDN 1 Kerumut, SDN 2 Kerumut, and SDN 3 Kerumut. The sample of this study was selected based on the students’ test result which was on low category. The technique of the data collection used interview and documentation. The result showed that students mathematic learning difficulties affected by internal and external factor of students. Keywords: Learning Difficulties, Learning Mathematic, Difficulties Factor in Learning